Zoledronic acid in patients with stage IIIA/B NSCLC: results of a randomized, phase III study - Scagliotti, Giorgio V.; Manegold, Christian (Annals of oncology, 2012)
Background: Bone metastases are common in patients with advanced non-small-cell lung cancer (NSCLC) and can have devastating consequences. Preventing or delaying bone metastases may improve outcomes. Patients and methods: This study evaluated whether zoledronic acid (ZOL) delayed disease progression or recurrence in patients with controlled stage IIIA/B NSCLC after first-line therapy. Patients received vitamin D and calcium supplementation and were randomized to i.v. ZOL (every 3–4 weeks) or no treatment (control). The primary end point was progression-free survival (PFS). Results: No significant intergroup differences were observed in PFS or overall survival (OS). Median PFS was 9.0 months with ZOL versus 11.3 months for control. Fifteen ZOL-treated (6.6%) and 19 control patients (9.0%) developed bone metastases. Estimated 1-year OS was 81.8% for each group. ZOL safety profile was consistent with previous clinical data, but with higher discontinuations versus control. Fifteen ZOL-treated (6.6%) and five control patients (2.3%) had renal adverse events. Two cases of osteonecrosis of the jaw were reported. Conclusions: ZOL did not significantly affect PFS or OS in stage IIIA/B NSCLC patients with controlled disease, with a trend toward worsening PFS in the longer-term follow-up. Few patients experienced bone metastases, possibly limiting the potential ZOL impact on disease course.
Gesehen am 19.09.2018